2023
DOI: 10.3390/w15081605
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Remote Sensing Techniques and Meteorological Data to Assess the Ideal Irrigation System Performance Scenarios for Improving Crop Productivity

Abstract: To increase agricultural productivity and ensure food security, it is important to understand the reasons for variations in irrigation over time. However, researchers often avoid investigating water productivity due to data availability challenges. This study aimed to assess the performance of the irrigation system for winter wheat crops using a high-resolution satellite, Sentinel 2 A/B, combined with meteorological data and Google Earth Engine (GEE)-based remote sensing techniques. The study area is located n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Sharma et al (2018) demonstrated the possibility of accurate identification of irrigated croplands through the combination of NDVI, NDMI, and EVI (enhanced vegetation index) within the framework of SVM (support vector machine) algorithm of machine learning. Application of NDMI is not limited to irrigation mapping, and it is also used in irrigation scheduling during crop cultivation, as Gaznayee et al (2023) reported its efficiency in irrigation control due to high sensitivity to changes in soil moisture. Verma & Verma (2023) also claim that remote sensing with NDMI could be used in precision agricultural systems to control and maintain soil moisture at the optimal level for cultivated crops.…”
Section: Introductionmentioning
confidence: 99%
“…Sharma et al (2018) demonstrated the possibility of accurate identification of irrigated croplands through the combination of NDVI, NDMI, and EVI (enhanced vegetation index) within the framework of SVM (support vector machine) algorithm of machine learning. Application of NDMI is not limited to irrigation mapping, and it is also used in irrigation scheduling during crop cultivation, as Gaznayee et al (2023) reported its efficiency in irrigation control due to high sensitivity to changes in soil moisture. Verma & Verma (2023) also claim that remote sensing with NDMI could be used in precision agricultural systems to control and maintain soil moisture at the optimal level for cultivated crops.…”
Section: Introductionmentioning
confidence: 99%
“…This technology enables the monitoring of agricultural fields at various spatial, temporal, and spectral resolutions, allowing for the identification of crop types, growth stages, and stress conditions [5]. As a result, remote sensing data can be harnessed to inform crop management strategies, such as irrigation scheduling, nutrient application, and pest control, which are essential for maintaining high productivity and environmental sustainability [6].…”
Section: Introductionmentioning
confidence: 99%